Integration of sulfate assimilation with carbon and nitrogen metabolism in transition from C3 to C4 photosynthesis - Jobe, Timothy O (Journal of experimental botany, 2019)
© The Author(s) 2019. Published by Oxford University Press on behalf of the Society for Experimental Biology.